Wound management and dressing selection in Stevens-Johnson syndrome and toxic epidermal necrolysis: a systematic review - Maiara C. Macagnan; Priscila de Cassia Francisco; Breno S. Kliemann; Adriano A. Mehl (Revista da Sociedade Portuguesa de Dermatologia e Venereologia, 2025)
Objectives: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe cutaneous adverse drug reactions, which lead to epidermal detachment and may be life-threatening. Apart from supportive and systemic treatment of the disease, appropriate dressing and wound management are essential for the care of patients with SJS/TEN. This study aims to assess which are the most used dressings for SJS/TEN, and how wound management can contribute to skin healing. Methods: Searches were performed in Cochrane Library, Embase, MEDLINE, and PubMed databases, using the following search terms: (SJS OR TEN) AND (Wounds OR Dressings). Information extracted on dressings was used as well as local care (including materials for cleansing, debridement, topical therapy, fixation, and time for dressing changing) and time for re-epithelialization. Results: A total of 17 articles published in the last 11 years were selected. Six (35.3%) mentioned silver- based topical therapies as treatment of choice. Allografts and porcine xenografts were cited by a further 6 (35.3%) studies, biosynthetic dressings with a combination of collagen mesh and silicone by 4 (23.5%), petrolatum-based products by 4 (23.5%), and patient’s own detached skin as a biological dressing by 2 (11.8%) studies. Conclusion: Upon analysis of collected data, it was noted that little information is available on topical treatment in SJS and TEN, with no consensus on an ideal protocol for such cases. Therefore, dressing management for these disorders remains a challenge in care, and further research on this subject should be encouraged.